Clinical Spectrum, Molecular Characterization, Antifungal Susceptibility Testing of Exophiala spp. From India and Description of a Novel Exophiala Species, E. arunalokei sp. nov - Singh, Shreya; Rudramurthy, Shivaprakash M.; Padhye, Arvind A.; Hemashetter, Basavaraj M.; Iyer, Ranganathan; Hallur, Vinaykumar; Sharma, Anuradha; Agnihotri, Sourav; Gupta, Sunita; Ghosh, Anup; Kaur, Harsimran (Frontiers in Cellular and Infection Microbiology, 2021)
Introduction: Exophiala spp. are important opportunist pathogens causing subcutaneous or even fatal disseminated infections in otherwise both immunosuppressed and healthy individuals but there are no systematic studies on the isolates of Exophiala species from India. Methods: Twenty-four isolates of Exophiala species were retrieved from the National Culture Collection of Pathogenic Fungi (NCCPF) and identified phenotypically and by molecular methods (ITS region sequencing) followed by antifungal susceptibility testing (AFST) CLSI-M38A3 guidelines. A review of the literature of cases from India was performed up to 1st January 2021 using the Medline and Cochrane database. Results: E. dermatitidis (n=8), E. jeanselmei (n=6), E. spinifera (n=6), E. mesophila (n=1), E. oligosperma (n=1), E. xenobiotica (n=1) were identified and the sequencing of ITS, β-tubulin and β-actin revealed a novel species, E. arunalokei sp. nov. (n=1). The ITS sequence phylogram of E. jeanselmei revealed that the majority (83%) formed a separate cluster close to type A while majority (75%) of E. dermatitidis were type B. The MIC (mg/L) of amphotericin, itraconazole, voriconazole, micafungin, caspofungin, anidulafungin and posaconazole, was 1, 0.25, 0.125, 0.12, 0.125, 0.062 and 0.062, respectively. Sixteen more cases were identified on the literature review and a significant association of E. dermatitidis with history of surgical procedures (p=0.013), invasive disease (p= 0.032) and of E. mesophila with tuberculosis (p=0.026) was seen. Conclusion: This, to the best of our knowledge is the first study from India elucidating the molecular and clinical characteristics of Exophiala species and the first Indian report of human infection due to E. xenobiotica and E. arunalokei